Technical skills for adventure programming : a curriculum guide - Wagstaff, Mark, ....-; Attarian, Aram, ....- (Champaign, IL : Human Kinetics, 2009)
If you're looking for a book that will improve your knowledge and technical instruction skills in land, water, and snow and ice sports and activities, this is it! Technical Skills for Adventure Programming: A Curriculum Guide is an all-in-one resource, based on current methods, that will guide you in becoming a skilled adventure instructor in the classroom and in the field. This book includes •comprehensive units with lesson plans for 12 popular outdoor adventure activities; •7 to 15 progressive, pedagogically sound lesson plans for each unit, featuring foundational teaching methods, experiential learning activities, and assessment strategies for adventure technical skills; •a CD-ROM with printable lesson plans and supporting materials for each unit that make it easy to print only what you will need in the field; and •an overview of the teaching process as it relates to adventure-based activities, including discussions of adventure education theory, learning styles, experiential learning and teaching, and outdoor teaching tips and considerations. Edited by nationally known outdoor adventure educators, this book allows you to tap into the knowledge and expertise of skilled instructors who present progressive technical skills for these activities: •Backpacking •Canoeing •Caving •Ice climbing •Mountain biking •Mountaineering •Nordic skiing •Rafting •Rock climbing •Sea kayaking •Snowshoeing •Whitewater kayaking
Throughout the guide, the expert instructors share insights, best practices, and field-tested lesson plans that help you teach essential skills to new outdoor and adventure enthusiasts. Lesson plans include a topic overview, equipment information, basic skill instruction, Leave No Trace practices, and safety considerations. You'll also find outcomes and assessment protocols for each lesson as well as information on modifying some of the activities to include people with disabilities. The format of the lessons provides you with the flexibility to select and use the plans and assessment strategies appropriate for your group's ages, ability levels, time constraints, and settings. Both a classroom and field-friendly guide, Technical Skills for Adventure Programming: A Curriculum Guide supports common practices and standards of the Wilderness Education Association, Outward Bound, Leave No Trace, the American Mountain Guide Association, the American Canoe Association, and the National Association for Sport and Physical Education. And it will prepare those with experience to confidently teach a dozen popular land-based, water-based, and winter activities.
Includes bibliographical references and index.
Keywords: Buitenactiviteiten; Buitensporten; Didactiek; Experiential learning -- Study and teaching -- Handbooks, manuals, etc; Outdoor education -- Study and teaching -- Handbooks, manuals, etc; Outdoor recreation -- Study and teaching -- Handbooks, manuals, etc; Recreation leaders -- Training of -- Handbooks, manuals, etc